A systematic review of the use of common behavioural interventions in oral health and diabetes management - Promise Ucheka; Ayse Basak Cinar; Jonathan Ling; 4. Richard Derek (Orapuh, Inc., 2021)
There has been a global rise in the prevalence of type 2 diabetes (T2DM) and it is expected to triple by 2030. Periodontal disease is one common complication of T2DM. As a result, there is potential for the use of common behavioural interventions in the management of both oral diseases and T2DM as a single intervention. To investigate the effectiveness of common behavioural interventions in the management of T2DM and oral diseases, and to synthesize the evidence of its effectiveness on both clinical and behavioural outcomes, a systematic review was conducted and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Data were extracted from MEDLINE, PsycARTICLES, and Web of Science. Only two studies met the preset inclusion criteria for the systematic review. In the intervention arms of both trials, there was a statistically significant reduction in HbA1c; and there were also improvements in glycaemic control, fasting blood glucose, and periodontal health. Although there is evidence in favour of the use of common behavioural interventions in the management of both oral diseases and T2DM, there is a need for more randomized controlled trials (RCTs) to investigate the use of common behavioural interventions using different populations, socioeconomic backgrounds, age groups, as well as provide a long-term follow-up.